2016
DOI: 10.5194/amt-9-4151-2016
|View full text |Cite
|
Sign up to set email alerts
|

Coupling sky images with radiative transfer models: a new method to estimate cloud optical depth

Abstract: Abstract. A method for retrieving cloud optical depth (τ c ) using a UCSD developed ground-based sky imager (USI) is presented. The radiance red-blue ratio (RRBR) method is motivated from the analysis of simulated images of various τ c produced by a radiative transfer model (RTM). From these images the basic parameters affecting the radiance and red-blue ratio (RBR) of a pixel are identified as the solar zenith angle (θ 0 ), τ c , solar pixel angle/scattering angle (ϑ s ), and pixel zenith angle/view angle (ϑ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Mejia et al . [] presented images of radiance from which they retrieved images of COD using a RT model, which likewise exhibited strong variation in COD on scales of 15 m (for assumed cloud base height of 1 km). Fine structure in cloud radiance, down to the limit of the resolution, estimated as about 1 m, was seen also in the film‐photographic images of Sachs et al [].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mejia et al . [] presented images of radiance from which they retrieved images of COD using a RT model, which likewise exhibited strong variation in COD on scales of 15 m (for assumed cloud base height of 1 km). Fine structure in cloud radiance, down to the limit of the resolution, estimated as about 1 m, was seen also in the film‐photographic images of Sachs et al [].…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental limitation of the approach is the inherent two dimensionality of the measurement, with no characterization of the vertical dimension. Another limitation for quantitative interpretation is that for clouds of optical depth greater than about 3, the inversion of radiance to optical depth becomes much more problematic than for optically thin clouds [ Mejia et al ., ]. Similar considerations obtain for situations with clouds at multiple levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The red-to-blue ratio (RBR; Figure 7-2, middle right) is often used as a main indicator for clouds because of their different spectral-scattering properties (high RBR) and clear-sky (low RBR) conditions (Shields, Johnson, and Koehler 1993;Long and DeLuisi 1998). Using radiative transfer modeling, Mejia et al (2016) demonstrated some ambiguity in the RBR method and proposed the radiance RBR method, which leverages intensities and RBR to identify cloudy pixels. Pixel intensities (Figure 7-2, middle left) are also related to cloud cover and might be exploited as an additional feature for cloud detection.…”
Section: -6mentioning
confidence: 99%